Human tendon adaptation in response to mechanical loading: a systematic review and meta-analysis of exercise intervention studies on healthy adults - Bohm, S.; Mersmann, F.; Arampatzis, A. (Sports Medicine - Open, 2015)
Background: The present article systematically reviews recent literature on the in vivo adaptation of asymptomatic human tendons following increased chronic mechanical loading, and meta-analyzes the loading conditions, intervention outcomes, as well as methodological aspects.